Pengaruh Aplikasi Absensi Online (SISENSI) terhadap Produktivitas Karyawan Melalui Kedisiplinan Karyawan Bagian Produksi Pada Perumda Air Minum Tirta Mayang Kota Jambi - Prio Prambudi; Hendriyaldi Hendriyaldi; Dian Mala Fithriani Aira (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to describe and analyze the influence of the online attendance application (Sisensi) on employee productivity through employee discipline in the production division of Perumda Air Minum Tirta Mayang, Jambi City. The method used is quantitative analysis with a population of employees and a sample of 94 respondents. Data were collected using a Likert scale–based questionnaire, and the analysis was conducted using the Structural Equation Modeling (SEM) technique based on Partial Least Squares (PLS) with the aid of SmartPLS 4 software. The results of the study show that: (1) the online attendance application has a positive and significant effect on employee productivity, (2) the online attendance application has a positive and significant effect on employee discipline, (3) employee discipline has a positive and significant effect on employee productivity, and (4) employee discipline is able to mediate the effect of the online attendance application on employee productivity. The recommendations derived from this study are as follows: For the employee productivity variable, it is suggested that the company provide relevant and continuous training, establish clear and easily understood Standard Operating Procedures (SOP), and conduct regular mentoring and evaluations to increase the amount of work that employees can complete. For the online attendance application variable, the company is advised to enhance the practicality and ease of use of the application, enabling employees to better understand and utilize the system. For the employee discipline variable, the company should conduct regular socialization sessions regarding the proper use of facilities and resources according to established standards to prevent damage, excessive use, and misuse.